2022
DOI: 10.4149/bll_2022_068
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and the impact of vaccination on mortality in COVID-19 patients

Abstract: INTRODUCTION:The novel coronavirus disease (COVID-19) pandemic has had a profound global impact economically, socially, and in many other areas. As vaccines are developed and introduced, their effect on the disease on both, the global and individual scale is a subject of intense curiosity. This study aimed to evaluate the relationship between risk factors for hospitalization, disease severity, and vaccination status in COVID-19 inpatients in a pandemic hospital. METHODOLOGY: Patients hospitalized for COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 17 publications
0
8
2
1
Order By: Relevance
“…Moreover, while age, CCI, and vaccination status were the independent factors associated with mortality in general cohort, CCI was the only independent factor in vaccinated patients. Similarly, in the study of Sezen et al, mortality was found to be significantly higher in patients with CCI ≥1 [15].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Moreover, while age, CCI, and vaccination status were the independent factors associated with mortality in general cohort, CCI was the only independent factor in vaccinated patients. Similarly, in the study of Sezen et al, mortality was found to be significantly higher in patients with CCI ≥1 [15].…”
Section: Discussionmentioning
confidence: 64%
“…However, studies comparing the mortality rates of vaccinated and unvaccinated patients, which take into account the demographic and clinical characteristics of patients in the delta variant dominant period, are limited. In the study of Sezen et al, mortality rates were higher in patients with advanced age, high CCI, and incomplete vaccination [15]. Alsaffar et al reported that vaccination significantly reduced the need for ICU admission (P 5 0.063, OR 5 0.476) and death (P 5 0.034, OR 5 0.378).…”
Section: Discussionmentioning
confidence: 96%
“…Many studies have revealed that COVID-19 patients with underlying diseases have increased risk of poor prognosis (15)(16)(17)(18). In the study of Yavuz et al, chronic pulmonary disease, malignancy, chronic kidney disease, and cardiovascular diseases were reported as independent risk factors for mortality (17).…”
Section: Discussionmentioning
confidence: 99%
“…hypertensive, immunosuppressed, and with chronic lung or heart diseases before COVID-19 are at greater risk of developing the severe condition and having a poor prognosis, requiring intensive care (8)(9)(10) .…”
mentioning
confidence: 99%
“…Despite the rapid development, production of vaccines, and effective treatments, COVID-19 continues to generate serious and widespread repercussions for health (8,11,12) . In cases considered to be symptomatic, the manifestations usually appear on the fifth day of infection, with a higher rate of hospitalization on the seventh day and worsening of the infection, evolving to ARDS on the eighth day (13) .…”
mentioning
confidence: 99%